2011
DOI: 10.1101/gr.111153.110
|View full text |Cite
|
Sign up to set email alerts
|

Diverse gene reprogramming events occur in the same spatial clusters of distal regulatory elements

Abstract: The spatial organization of genes in the interphase nucleus plays an important role in establishment and regulation of gene expression. Contradicting results have been reported to date, with little consensus about the dynamics of nuclear organization and the features of the contact loci. In this study, we investigated the properties and dynamics of genomic loci that are in contact with glucocorticoid receptor (GR)-responsive loci. We took a systematic approach, combining genome-wide interaction profiling by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
137
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 32 publications
19
137
0
Order By: Relevance
“…GR binding also coincides with hypersensitive sites (John et al 2008Grøntved et al 2013), and it was previously demonstrated that the majority of long-range genomic contacts involve hypersensitive sites (Hakim et al 2011). Considering the dynamics in chromatin accessibility observed here, we hypothesized that it could play a role in gene transcription regulation from a distance.…”
Section: Discussionmentioning
confidence: 95%
“…GR binding also coincides with hypersensitive sites (John et al 2008Grøntved et al 2013), and it was previously demonstrated that the majority of long-range genomic contacts involve hypersensitive sites (Hakim et al 2011). Considering the dynamics in chromatin accessibility observed here, we hypothesized that it could play a role in gene transcription regulation from a distance.…”
Section: Discussionmentioning
confidence: 95%
“…Note however that genes positioned within 1 μm of each other in a fixed cell will occasionally be much closer in live cells due to the diffusion of chromatin, which is known to occur in the submicron to micron range [51]. Indeed, it has been shown that interaction signals measured by 4C robustly correlated with distances of up to 1 μm as measured by 3D DNa-FISh [52].…”
Section: Factors Influencing Shared Gene-gene Neighborhoodsmentioning
confidence: 94%
“…Similarly, epigenetic modifications encompassing large domains of the genome have been described to participate in gene silencing and, more recently, gene activation during the process of malignant transformation (Hon et al 2012). Previous studies on the spatial organization of glucocorticoid response in murine cells showed that the hormonal response was facilitated by a preorganized conformation of the nucleus, particularly by cell type-specific chromatin sites accessible to regulatory factors (Hakim et al 2011). We postulate that the initial organization of TADs could act as topological constraint for changes in gene expression in response to external cues.…”
Section: Discussionmentioning
confidence: 99%
“…These genes, which can be located on different chromosomes, are organized in spatial clusters and preferentially transcribed in the same ''factories'' (Osborne et al 2004(Osborne et al , 2007Cavalli 2007). Whether such mechanisms participate in transient modifications of the transcription rate in differentiated cells responding to external cues is still unclear (Fullwood et al 2009;Kocanova et al 2010;Hakim et al 2011). Transient regulation of gene expression at the transcription level depends on the establishment of regulatory Ó 2014 Le Dily et al This article is distributed exclusively by Cold Spring Harbor Laboratory Press for the first six months after the full-issue publication date (see http://genesdev.cshlp.org/site/misc/terms.xhtml).…”
mentioning
confidence: 99%